2004
DOI: 10.1021/ar030240u
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization of CO2 and Epoxides Catalyzed by Metal Salen Complexes

Abstract: The design of efficient metal catalysts for the selective coupling of epoxides and carbon dioxide to afford completely alternating copolymers has made significant gains over the past decade. Hence, it is becoming increasingly clear that this "greener" route to polycarbonates has the potential to supplement or supplant current processes for the production of these important thermoplastics, which involve the condensation polymerization of diols and phosgene or organic carbonates. On the basis of the experiences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
208
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 454 publications
(211 citation statements)
references
References 39 publications
3
208
0
Order By: Relevance
“…[5] Over the last decade the use of homogeneous catalysts has lead to a drastic increase in catalytic activities. [6][7][8] For the copolymerization of CO 2 and propylene oxide, salen complexes, especially of chromium [9,10] and cobalt [11][12][13] have come into focus. Yet, the highest activities for the alternating copolymerization of CO 2 and cyclohexene oxide so far have been reached by Coates' bdiketiminato (BDI) zinc complexes (see below).…”
Section: Introductionmentioning
confidence: 99%
“…[5] Over the last decade the use of homogeneous catalysts has lead to a drastic increase in catalytic activities. [6][7][8] For the copolymerization of CO 2 and propylene oxide, salen complexes, especially of chromium [9,10] and cobalt [11][12][13] have come into focus. Yet, the highest activities for the alternating copolymerization of CO 2 and cyclohexene oxide so far have been reached by Coates' bdiketiminato (BDI) zinc complexes (see below).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to producing PCHC, the copolymerization reactions catalyzed by 1-4 also led to the production of cyclic cyclohexene carbonate (CCHC) as a byproduct. This is generally the result of back-biting of the growing copolymer chain [27].…”
Section: Ring-opening Copolymerization Of Co2 and Cho With Complexes 1-4mentioning
confidence: 99%
“…Inoue et al first reported the synthesis of high molecular weight polycarbonates by alternating copolymerization of CO 2 and epoxides using a catalyst derived from diethyl zinc and water [116]. Since then, several excellent reviews [117][118][119][120][121] have appeared on this interesting topic. It is demonstrated that coordination compounds based on zinc, aluminum, cadmium, chromium, manganese, cobalt, and rare-earth metals are promising candidates for highly active catalytic systems for the copolymerization of epoxides with CO 2 .…”
Section: Polycarbonate Synthesis In/by Ilmentioning
confidence: 99%